Alkylglycerols modulate the proliferation and differentiation of non-specific agonist and specific antigen-stimulated splenic lymphocytes. - Linxi Qian; Mingshun Zhang; Shengmei Wu; Yan Zhong; Eric Van Tol; Wei Cai (PLoS ONE)
Alkylglycerols (AKGs) are ether-linked glycerols derived from shark liver oil and found in small amounts in human milk. Previous studies showed that oral AKGs administration significantly increased the immune response in mice. The aim of the present study was to investigate the in vitro immunomodulatory effect of AKGs on stimulating splenic lymphocyte responses. C57BL/6 mice were immunized with hepatitis B surface antigen (HBsAg). Splenic B cells were purified and stimulated with anti-BCR and anti-CD38. Meanwhile, splenic CD4+ T cells were purified and stimulated with anti-CD3 and anti-CD28. For antigen specific stimulation, the purified CD4+ T cells were cocultured with HBsAg -pulsed dendritic cells. The stimulated lymphocytes were treated with different concentrations of AKGs. The cell proliferation was assessed by [3H]-thymidine incorporation assay. The maturation of B cells was assessed by examining the germline (GL) transcription of IgG (γ1) mRNA expression, and the surface expressions of CD80/CD86 markers were examined by flow cytometry analysis. Th1/Th2 polarity was assessed by T-BET (Th1)/GATA-3 (Th2) flow cytometry assay and by characteristic cytokines ELISA assay (TNF-α and IFN-γ for Th1; IL-4 and IL-10 for Th2). It was found that AKGs significantly increased the BCR/CD38 -stimulated B cell proliferation. The T cell proliferation in response to CD3/CD28 or specific antigen stimulation was also increased by AKGs. The transcriptional level of IgG (γ1) and the expressions of CD80/CD86 molecules were markedly increased by AKGs in BCR/CD38 -stimulated B cells. Meanwhile, the results showed that AKGs increased the expression of T-BET transcriptional factor and the production of Th1 cytokines (TNF-α and IFN-γ) upon CD3/CD28 stimulation; whereas, levels of Th2 cytokines (IL-4 and IL-10) were decreased by AKGs. Our study demonstrated that AKGs can modulate immune responses by boosting the proliferation and maturation of murine lymphocytes in vitro.